The influence of a reward programme on attitudinal loyalty in the South African commercial cheque card market. - Naidoo, Prenolan (My University, 2014)
ABSTRACT A reward programme aims to improve customer loyalty from an attitudinal and behavioural perspective. Substantial research has explored this relationship in the business-to-consumer environment. The loyalty influence of reward programmes in the business-to-business environment has not been explored as extensively. In the context of the banking industry, most loyalty studies focus on credit card loyalty programmes applicable to the consumer environment. The purpose of this research was to assess the influence of a reward programme on attitudinal and behavioural loyalty in the commercial cheque card market. Behavioural loyalty could easily be determined based on the available customer spending patterns. To assess attitudinal loyalty a more complex approach was required which entailed development of an online survey. Data collected from the online survey was analysed to define a single measure of attitudinal loyalty, and this information then paired with the corresponding behavioural measure for each respondent. The primary research objectives were then assessed using the information gathered. The research showed that commercial cheque cardholders linked to the loyalty programme consistently displayed lower levels of attitudinal loyalty and higher levels of behavioural loyalty. In addition, it was found that as company size increased, the influence of the loyalty programme on attitudinal loyalty decreased. The attitudinal loyalty findings of the study differed from those of a similar study conducted amongst commercial credit cardholders. This highlighted the different influence which the same loyalty programme can have on credit cardholders versus cheque cardholders. As this was unexpected, it offers an opportunity for further research to be conducted in to the type of rewards programme which would be most appealing to commercial cheque cardholders.
MBA 2013
Keywords: Bank marketing,Customer loyalty programs,Debit cards.